Pemanfaatan Ketahanan Pangan Pada Budidaya Ikan Lele Sebagai Bentuk Upaya Penanggulangan Balita Stunting di Desa Protomulyo - Qothrun Nada Zahrotun Nabila; Nabila Tri Septiana; Cucu Febry Astriyani; Aisha Rachmadian Puteri; Indra Purwanto; Widi Cahya Adi (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the problems in Indonesia that is still being discussed is stunting. The prevalence of stunting in Indonesia is supported by data from the Ministry of Health in 2021 which reached 24.4%, in 2022-2023 it will fall to 21.6%, and the government hopes that in 2024 it can fall to 14%. Stunting is not only about the problem of a child's height, but is more serious, which has an impact on the individual's quality of life due to malnutrition, which can lead to chronic diseases and a decrease in the child's intelligence level. This can affect the body and brain. Based on research in Protomulyo Village, it was found that the prevalence of babies below the red line was 27 under five, which occurred in babies aged 0 months-5 years. Establishment of food security in catfish cultivation in Protomulyo Village, District. South Kaliwungu can be a solution and can overcome the problem of stunting toddlers. Because catfish has a high protein content. The research method used is a qualitative method by conducting interviews and literature studies. The aim of this research is to determine the process of cultivating food security in catfish, the economic impact on food security in cultivating catfish, and the benefits of catfish as a form of effort to overcome stunting in toddlers